การพัฒนาสื่อเทคโนโลยีจัดการศึกษาเพื่อพัฒนาคุณภาพชีวิตผู้สูงอายุ จากการมีส่วนร่วมของชุมชน ในเขตชานเมือง เทศบาลเมือง จังหวัดลำปาง / The Development of Media Technology for Education Management to Improve the Life Quality of Elderly by Public Participation - Buakanok, Fisik Sean; wonguparaj, Kaset (Journal of Community Development Research (Humanities and Social Sciences); Vol 10 No 4 (2560): October-December 2017, 2017)
การวิจัยครั้งนี้เป็นความพยายามพัฒนาสื่อเทคโนโลยีจัดการศึกษาสำหรับผู้ดูแลผู้สูงอายุ ให้มีความรู้ความเข้าใจในการพัฒนาคุณภาพชีวิตผู้สูงอายุ โดยวัตถุประสงค์ เพื่อ 1) ศึกษาบทบาทและความจำเป็นในการนำสื่อเทคโนโลยีมาใช้ในการจัดการศึกษาเพื่อการพัฒนาคุณภาพชีวิตผู้สูงอายุ 2) พัฒนาสื่อเทคโนโลยีจัดการศึกษาเพื่อการพัฒนาคุณภาพชีวิตผู้สูงอายุจากการมีส่วนร่วมของชุมชน 3) ศึกษาผลของสื่อเทคโนโลยีจัดการศึกษาในการพัฒนาคุณภาพชีวิตผู้สูงอายุจากการมีส่วนร่วมของชุมชน เป็นการวัดผลสัมฤทธิ์การเรียนรู้ของกลุ่มตัวอย่างผู้ดูแลผู้สูงอายุหลังใช้สื่อ ทำการทดลองแบบกลุ่มเดียววัดผลหลังทดลอง (One–Shot Case Study) ตัวอย่างที่ใช้ศึกษาจำนวน 100 คน แบ่งเป็นกลุ่มตัวอย่างร่วมผลิตสื่อ จำนวน 50 คน ได้มาโดยการคัดเลือกแบบเจาะจง และกลุ่มตัวอย่างผู้ใช้สื่อ จำนวน 50 คน ได้มาโดยวิธีสุ่มอย่างง่าย เครื่องมือที่ใช้ได้แก่ การสนทนากลุ่ม การสัมภาษณ์ แบบประเมินคุณภาพสื่อ แบบทดสอบวัดผลสัมฤทธิ์การเรียนรู้ สถิติในการวิเคราะห์ ประกอบด้วย ร้อยละ, ค่าเฉลี่ย , ค่าส่วนเบี่ยงเบนมาตรฐาน (S.D.) และ t-test ซึ่งเป็นการทดสอบค่าเฉลี่ยของกลุ่มตัวอย่าง 1 กลุ่มเทียบกับเกณฑ์ร้อยละ 70 ได้ผลดังนี้      1. บทบาทและความจำเป็นของสื่อเทคโนโลยีจัดการศึกษา คือ ทำให้ชุมชนได้รับทราบข้อมูล สร้างความตระหนัก ส่งเสริมทัศนคติค่านิยม สร้างการร่วมมือในการเรียนรู้ จนทำให้เกิดการเปลี่ยนพฤติกรรม      2. สื่อเทคโนโลยีจัดการศึกษา “เกมการเรียนรู้” มีประสิทธิภาพรายบุคคล 76.25/78 ประสิทธิภาพกลุ่มย่อย 73.87/79.8 และผลการประเมินคุณภาพสื่อค่าเฉลี่ยรวม 3.94 ความเหมาะสมระดับมาก      3. ผลของสื่อเทคโนโลยีจัดการศึกษา ผู้ดูแลผู้สูงอายุที่เรียนรู้ด้วยสื่อเกมการเรียนรู้มีคะแนนเฉลี่ยผลสัมฤทธิ์การเรียนรู้แตกต่างกันอย่างมีนัยสำคัญที่ 0.05 (t(49) = 4.177, p < .001)      This research is an educational media development effort for elderly caregivers to improve their knowledge and understanding of the quality of life for the elderly. The purposes were to: 1) Study the role and necessity of bringing media technology for education management to improve the life quality of elderly, 2) Develop the media technology for education management to improve the life quality of elderly by Public Participation, and 3) Study the effects of the media technology for education management. Research population is populations in Suburban area, Lampang municipality, Lampang Province. The research design was One–Shot Case study. One hundred of research samples divided into two groups. One group to engaging media production of 50 people were selected by Purposive Sampling. The other group were media users of 50 people selected by simple random sampling. Research materials were Focus Group Discussion, Interview, Media Quality Assessment, and Learning achievement test. The methodology was One–Shot Case study, making Developmental Testing, and Learning achievement Testing. Statistical analysis consists of percentage, mean (), standard deviation (S.D.) and t-test which were average test of one sample group compared to 70%. The results were as follows:      1. The role and necessity of media technology for education management are: To get the community informed, Raise awareness, Promote attitude, Create collaborative learning, and finally changing of their behavior      2. The media technology for education management “learning games” were effective in individual group 76.25/78, effective in small group 73.87/79.8, and the mean score of media quality evaluation was 3.94 which was in a very appropriate scale.      3. For the effects of the media technology for education management, the elderly caregivers who learn with learning game was statistically significant at 0.05 level (t (49) = 4.177, p < .001).
Keywords: Media technology for education management; Public Participation: The life quality of elderly.